Tourism, Wages, and Poverty in the Special Region of Yogyakarta - Widyanirwasita, Gayatri; Syafitri, Wildan (Journal of Development Economic and Social Studies, 2026)
This research was conducted with the aim of determining the influence of Tourism, Minimum Wages, and Open Unemployment Rates on Poverty in districts/cities in the Special Region of Yogyakarta Province. The type of data used as the object of research in this study is panel data. The data in this study uses data from 5 Districts/Cities in the Special Region of Yogyakarta Province during the period 2013-2024. The data used are secondary data sourced from official institutions as the Central Statistics Agency (BPS) and Tourism Statistics by the Yogyakarta Provincial Tourism Office. This study was conducted with a quantitative approach using the panel data regression method. The findings in this study indicate that an increase in the Tourism sector and Minimum Wages will have an impact on reducing Poverty in districts/cities in the Special Region of Yogyakarta Province. On the other hand, an anomaly was found in the Open Unemployment Rate because it had no influence on poverty in districts/cities in the Special Region of Yogyakarta Province during the 2013-2024 period.